Disruption of Yarrowia lipolytica biofilms by rhamnolipid biosurfactant - Dusane, Devendra H (BioMed Central, 2012)
BACKGROUND: Yarrowia lipolytica is an ascomycetous dimorphic fungus that exhibits biofilm mode of growth. Earlier work has shown that biosurfactants such as rhamnolipids are efficient dispersants of bacterial biofilms. However, their effectiveness against fungal biofilms (particularly Y. lipolytica) has not been investigated. The aim of this study was to determine the effect of rhamnolipid on a biofilm forming strain of Y. lipolytica. Two chemical surfactants, cetyl-trimethyl ammonium bromide (CTAB) and sodium dodecyl sulphate (SDS) were used as controls for comparison. RESULTS: The methylene blue dye exclusion assay indicated an increase in fungal cell permeability after rhamnolipid treatment. Microtiter plate assay showed that the surfactant coating decreased Y. lipolytica biofilm formation by 50%. Rhamnolipid treatment disrupted pre-formed biofilms in a more effective manner than the other two surfactants. Confocal laser scanning microscopic studies showed that biofilm formation onto glass surfaces was decreased by 67% after sub-minimum inhibitory concentration (sub-MIC) treatment with rhamnolipids. The disruption of biofilms after rhamnolipid treatment was significant (P<0.05) when compared to SDS and CTAB. CONCLUSION: The results indicate a potential application of the biological surfactant to disrupt Y. lipolytica biofilms.